OCCURRENCE OF DEEP-WATER LEATHERJACKET FISH Thamnaconus tessellatus (GUNTHER, 1880) (TETRAODONTIFORMES: MONACANTHIDAE) FROM BITUNG, INDONESIA - Teguh Peristiwady (Jurnal Iktiologi Indonesia, 2008)
Occurrence of Deep-water Leatherjacket Fish Thamnaconus tessellatus (Gunther, 1880) (Tetraodontiformes: Monacanthidae) From Bitung, Indonesia. One specimen of Thamnaconus tessellatus (CRDOA 6367; 204.00 mm SL) was collected from Winenet Fish Market, Bitung, North Sulawesi, Indonesia, on 11 February 2008. The specimen was collected from depths of about 20-30 m in association with other coral reef fishes catch. This genus is poorly known because of their generally deep-water habitats and normally on the trawling grounds. The deepest record for the genus is collected by trawl net at a depth of 360 m (Fiji), 270 m (Loyalty Island) and between (230-260) m (New Caledonian). Found in many locations in southern Japan southward through the Ogasawara Islands, Malaysia, Taiwan, Hong Kong, Philippines, Indonesia and Papua New Guinea to Australia and New Caledonia. Its morphological features and diagnostic characters are discussed and illustrated.